Distributions of carbon and nitrogen isotopes in Scotland's topsoil: a national‐scale study. (10th September 2015) - Thornton, B.; Martin, G.; Procee, M.; Miller, D. R.; Coull, M.; Yao, H.; Chapman, S. J.; Hudson, G.; Midwood, A. J.
Summary: The land use and climate of Scotland are currently undergoing change. Concentrations of Natural abundance stable isotopes in ecosystems have been used extensively to help to understand a wide range of processes and functions. In the current study topsoil was collected from the intercepts of a 20‐km grid across the whole of Scotland (183 points), which encompass large differences in mean annual temperature (MAT, 3.1–9.1°C), mean annual precipitation (MAP, 588–3470 mm) and land use (from arable land through grassland and woodland to less fertile moorlands and bogs). At each sampling point the natural abundance δ 13 C and δ 15 N values were measured. This paper describes for the first time the spatial distribution of these isotopes in the topsoil of Scotland. We applied linear modelling to assess the extent to which land use and climate can control the observed distributions. The more enriched topsoil δ 13 C values occurred in the northern and western regions of Scotland. Topsoil δ 13 C values were tightly constrained about the mean, and possibly because of this we were able to explain only 23.6% of the variance even after considering the potential effects of a wide range of abiotic factors and land uses. Precipitation and land use explained the greatest variance in topsoil δ 13 C, but individually this was only 10.4 and 9.9%, respectively. Topsoil δ 15 N values showed a more complex spatial arrangement. The main areas of the more enriched δ 15 N values were in the northern isles, along or near the coast on the eastern side of the country and in some areas of the western mainland. For topsoil δ 15 N, all explanatory variables together explained 55.7% of the variance, with land use alone explaining 45.4%. Soil under arable land and improved grassland, the more fertile sites, had the most enriched δ 15 N values, whereas woodland and bogs had the most depleted values. A positive relationship between topsoil δ 15 N and potential rate of nitrification suggested that this was due, at least in part, to greater losses of nitrate under arable land and improved grassland.